The use of artificial intelligence in database and knowledge sytems - an analysis of machine learning, neural networks, and other ai methods for database and knowledge analysis - Haba, Oleh (Комп’ютерне моделювання та інформаційні технології, 2023)
This presentation explores the use of artificial intelligence (AI) in database and knowledge systems, with a focus on the applications of machine learning, neural networks, and other AI methods for data and knowledge analysis. Machine learning allows computers to learn from data and make predictions, while neural networks excel in natural language processing. Processing large volumes of data with AI simplifies analysis and provides personalized recommendations. Furthermore, AI aids in automating the analysis of natural data, such as medical images. The presentation concludes by emphasizing the profound impact of AI on contemporary data management and knowledge utilization.